Solar Power Plant Installation with Environmental Monitoring System to Increase Hydroponic vegetable production - Sundawa, Bakti Viyata; Hutabarat, Nicodemus Firman River; Cholish (International Journal of Research in Vocational Studies (IJRVOCAS), 2024)
The demand for vegetables in Batubara Regency is extremely high. Currently, the supply of vegetables is still imported from Tanah Karo and Deli Serdang Regency. This is due to the geographical condition of Batubara Regency which is in a coastal area. The majority of their people work in the fisheries sector. This opportunity was taken by our partner from SMK T. Amir Hamzah Indrapura by building greenhouse to produce vegetables. However, there are obstacles, namely the partner does not have a cheap source of electricity to increase the production of hydroponic vegetables. Therefore, it is necessary to build an alternative electricity source in the form of a solar power plant. It saves monthly electricity costs at the greenhouse. An environmental monitoring system needs to be built at the greenhouse to maintain and monitor the parameters that affect the growth requirements of hydroponic vegetables such as temperature, humidity, and lighting.